Implementation of Good Governance Principles in Public Service Management at the Department of Youth and Sports in Bandung City - Rahmat Soleh; Arry Muhammad Syukur; Neneng Widya Amelia (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The goal of this study is to examine how the Bandung City Youth and Sports Agency (Dispora) applies good governance principles to public service administration. For effective, efficient, accountable, and responsive government to the requirements of the public, the idea of good governance is a crucial point of reference. The policy implementation theory of Grindle (1980) serves as the foundation for the analysis in this qualitative descriptive study. This theory highlights the significance of the implementation environment and policy context, which includes the players, resources, and implementing institutions' attributes. A review of the literature, observation, and interviews with community members and officials who used Dispora services were used to gather data. The results indicate that the implementation of good governance principles has been carried out in terms of transparency, accountability, and public participation. However, obstacles remain in terms of effective inter-departmental coordination, human resource capacity, and optimization of the digital service system. The implications of this study emphasize the importance of bureaucratic reform and institutional capacity building in creating higher-quality public services that are oriented toward public satisfaction.